INTERNALISASI INTERNALISASI PENDIDIKAN AKHLAK PADA ANAK MELALUI KEGIATAN JAM’IYAH DIBA’IYAH DI DESA REJOAGUNG NGORO JOMBANG - M. Anang Ma'ruf (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2019)
The appreciation of moral education is aimed at character building (morals). The problem raised in this study is the internalization of moral education among the children through religious activities namely jam'iyah diba'iyah and its relevance to Islamic religious education. The results of the study showed that the values ??of moral education were polite, dressed, polite, talk in and out of assembly, the manner to walk in front of other members who are older, the manner of Mushofakhah, eating and drinking, the essence is the teachings of Islam itself try to be internalized in jam'iyah diba'iyah through its methods. The process of internalizing moral education in children through jam'iyah diba'iyah uses the habituation by several stages, namely: approaching members. Delivering mauidhoh hasanah and uswatun hasanah or education advice. Giving a warning. Providing punishment (education by being given punishment) which is educational.